Diels–Alder Reversible Thermoset 3D Printing: Isotropic Thermoset Polymers via Fused Filament Fabrication. (26th April 2017) - Yang, Kejia; Grant, Jesse C.; Lamey, Patrice; Joshi‐Imre, Alexandra; Lund, Benjamin R.; Smaldone, Ronald A.; Voit, Walter
Abstract : This study presents a new 3D printing process, the Diels–Alder reversible thermoset (DART) process, and a first generation of printable DART resins, which exhibit thermoset properties at use temperatures, ultralow melt viscosity at print temperatures, smooth part surface finish, and as‐printed isotropic mechanical properties. This study utilizes dynamic covalent chemistry based on reversible furan‐maleimide Diels–Alder linkages in the polymers, which can be decrosslinked and melt‐processed during printing between 90 and 150 °C, and recrosslinked at lower temperatures to their entropically favored state. This study compares the first generation of DART materials to commonly 3D printed high‐toughness thermoplastics. Parts printed from typical fused filament fabrication compatible materials exhibit anisotropy of more than 50% and sometimes upward of 98% in toughness when deformed along the build direction, while the first generation of DART materials exhibit less than 4% toughness reduction when deformed along the build direction. At room temperature, the toughest DART materials exhibit baseline toughness of 18.59 ± 0.91 and 18.36 ± 0.57 MJ m −3 perpendicular and parallel to the build direction, respectively. DART printing will enable chemists, polymer engineers, materials scientists, and industrial designers to translate new robust materials possessing targeted thermomechanical properties, multiaxial toughness, smooth surface finish, and low anisotropy. Abstract : A new process called Diels–Alder reversible thermoset (DART) 3D printing, adapted from fused filament fabrication and based on dynamic, covalent chemistries, and a first generation of printable DART resins are demonstrated with thermoset properties at use temperatures up to 80 °C, superior surface finish, isotropism, and tough mechanical properties along the build direction of 18.36 ± 0.57 MJ m −3 .